Current situation of marijuana use in adolescents and its implications for nursing - Medina Quevedo, Pablo (2023)
Support for the legalization of marijuana has increased around the world. Although, one of the concerns about the proposal regarding the legalization of medical and recreational marijuana use is the potential increase in consumption and related damages in the population after its legalization. Just over 10 years after the legalization of marijuana use in the United States and some other parts of the world, it has been a great challenge for health professionals. This essay presents a perspective of the current situation of the phenomenon in the adolescent population, from which some implications for the nursing profession are proposed.